Qualitative exploration of self-assessment in natural science: Grade 6 learners' experiences in rural Kwa-Zulu Natal classrooms - Preya Pillay (Interdisciplinary Journal of Rural and Community Studies)
Self-assessment, a crucial metacognitive skill for self-regulated learning, is vital for academic growth, especially in challenging subjects like Natural Science. However, its implementation and effectiveness in rural South African primary schools remain underexplored. This study investigates Grade 6 learners' experiences of self-assessment in Natural Science at two rural schools in KwaZulu-Natal, South Africa. Employing a qualitative multiple case study design, the research utilised semi-structured interviews and classroom observations with twelve purposively selected Grade 6 learners. The study reveals that while learners generally perceive self-assessment positively, they struggle with effective implementation due to a superficial understanding and difficulties in objective self-evaluation. The rural context presents significant challenges, particularly the lack of practical science equipment, which hinders learners' ability to engage in hands-on experiments and accurately assess their understanding. Furthermore, traditional knowledge and cultural values sometimes conflict with the scientific methods taught in schools, creating confusion in the self-assessment process. These findings indicate that effective self-assessment in rural Natural Science education is impeded by both institutional factors (resource limitations, inadequate teaching methods) and personal challenges (lack of confidence, cultural conflicts). Recommendations include developing context-specific, age-appropriate self-assessment tools, implementing strategies to bridge traditional and scientific knowledge, and creating innovative approaches to maximise limited resources in rural schools. This study contributes to the understanding of self-assessment practices in resource-constrained rural environments and offers insights for enhancing its effectiveness in similar contexts, addressing a gap in the existing literature on rural education and self-assessment in developing countries.